Analysis of postoperative ultrasonography surveillance after total thyroidectomy in patients with papillary thyroid carcinoma: a multicenter study. (February 2018) - Ryoo, Inseon; Kim, Dong Wook; Lee, Chang Yoon; Huh, Jung Yin; Lee, Song; Ahn, Hye Shin; Sung, Jin Yong
Background: In papillary thyroid carcinoma (PTC) patients, postoperative ultrasonography (US) surveillance is recommended at intervals of six or 12 months even though evidence is weak. Purpose: To determine the optimal interval of postoperative US surveillance in patients after total thyroidectomy for the treatment of PTC using multicenter data. Material and Methods: A total of 1400 patients from seven tertiary hospitals who underwent total thyroidectomy for treatment of PTC were included. Based on a retrospective review of clinical and pathologic results, multiple factors were analyzed according to recurrence/persistence or no recurrence/persistence. In recurrence/persistence group, the interval and number of follow-up US sessions in the initial detection of recurrence/persistence were investigated. Results: Of the 1400 patients, 115 (8.2%) showed tumor recurrence/persistence on follow-up US. Of 115 recurrence/persistence cases, 89 (77.4%) were initially detected on US: nodal recurrence/persistence (n = 92), non-nodal recurrence/persistence (n = 22), and both (n = 1). Among the clinical and pathologic factors, only tumor size and N stage were significant predictors for recurrence/persistence. In the recurrence/persistence group, the mean interval and number of follow-up US sessions in the initial detection of recurrence/persistence was 22.3 ± 16.8 months and 2.2 ± 1.9, respectively. Approximately two-thirds of recurrence/persistence cases (76/115, 66.1%) were detected in follow-up US within two years after total thyroidectomy. Conclusion: In PTC patients after total thyroidectomy, the optimal interval of the first US follow-up may be one to two years after thyroid surgery, and the appropriate number of postoperative US surveillance sessions within the first five years may be only one or two.